Effect of Topical Application of Hydro-Ethanolic Extract of Acacia nilotica Pods on Second-Degree Cutaneous Infected Burns - Kossi Metowogo; Tchin Darré; François Daubeuf; Povi Lawson-Evi; Kwashi Eklu-Gadegbeku; Kodjo A. Aklikokou; Gado Napo-Koura; Nelly Frossard; Messanvi Gbeassor (Journal of Pharmacy and Nutrition Sciences, 2015)
Acacia nilotica is a medicinal plant used traditionally in Togo to treat various diseases including burn wounds. The aim of this study was to evaluate experimentally Acacia nilotica burn wound healing effect. Cutaneous burn wounds were symmetrically caused on depilated areas of rat skin through contact with an aluminum bar (r = 10 mm), preheated at 80°C for 30 sec. Five groups of animal were constituted and each group contained 8 mice. Four groups of animal’s burn wounds were infected by Staphylococcus aureus. One group burn wound is uninfected and serves as negative control. Burn wounds were assessed by planimetry and histological parameters of healing. Twelve days after burn wound induction, wound contraction in the uninfected groups (negative control) was 19.9% for topical application against -2.43% for infected control. In the infected groups treated with extract, wound contraction was generally stimulates. Histological examination showed granulated tissue developing over the wounds treated with the extract of A. nilotica at 2.5% and 5% where the proliferation of fibroblasts and neo-blood vessels was very marked. In conclusion, A. nilotica pod contents tannin, flavonoids, alkaloids and protein reduces DPPH solution and significantly accelerates wound healing of burns, and this is the case even if wounds are infected with 109CFU/mL of S. aureus.